Donor selection for allogeneic hematopoietic cell transplantation - Fleischhauer, Katharina; Tran, Thuong Hien; Meisel, Roland; Mytilineos, Joannis; Dreger, Peter; Kröger, Nicolaus (Deutsches Ärzteblatt, 2023)
BACKGROUND: In Germany, each year over 3000 patients with malignant and non-malignant hematologic and systemic diseases are treated by allo - geneic hematopoietic cell transplantation (HCT). Genetic donor-recipient disparities, especially those concerning variable human leukocyte antigens (HLA), mediate both an immunotherapeutic effect and the risk of damage to healthy tissues ("graft-versus-host disease"). The adoption of evidencebased strategies for donor selection has been crucial for the continuous improvement of survival rates after allogeneic HCT, with over 50% of patients transplanted for standard indications-such as early-stage acute myeloid leukemia-alive at three years post-transplant. METHODS: The PubMed database was selectively searched for literature on immunogenetic and clinical factors relevant to allogeneic HCT, as part of the process of establishing a German consensus statement on HCT donor selection. RESULTS: The most important factor in donor selection is a match for the five major HLA loci (HLA-A, -B, -C, -DR, -DQ), either in genetically HLAidentical siblings or in unrelated but fully HLA-compatible donors from international registries. Additional selection criteria for the latter include com - patibility for the HLA-DP locus, donor age and sex, cytomegalovirus serostatus, and blood group. Related donors identical for only 50% of the HLA genes (haploidentical donors) as well as unrelated donors with a single HLA mismatch are both valid alternatives although they are associated with an up to 10% higher risk of mortality. CONCLUSION: The refinement of donor selection strategies has been instrumental for the continuous improvement of patient survival rates after allogeneic HCT witnessed over the past decades. An interdisciplinary approach to donor selection based on up-to-date scientific evidence is crucial for optimizing patient outcomes.